Serum levels of eosinophilic cationic protein (ECP), myeloperoxidase (MPO), lipid peroxidation products, interleukin (IL)-5 and interferon (IFN)-γ in children with bronchial asthma at acute asthma attack and remission - Kalaycı, Ömer; Saraçlar, Yıldız; Kılınç, Kamer; Şekerel, Bülent E. (The Turkish Journal of Pediatrics, 2000)
We determined serum levels of myeloperoxidase (MPO), eosinophilic cationic protein (ECP), reactive oxygen species measured as thiobarbituric acid reactive substances (TBARS), interleukin (IL)-5, and interferon (IFN)-γ in 14 asthmatic children during an asthma attack and remission. Twelve healthy children served as controls. In atopic asthmatics, asthma attack resulted in significant elevations of ECP, MPO, and TBARS compared to remission. TBARS levels were also higher at remission compared to controls. However, there was a great deal of overlap in the values of asthmatics and controls. IL-5 and IFN-γ were detectable at low levels and only in a few patients. These results provide further evidence for participation of eosinophils, neutrophils and reactive oxygen species in the pathogenesis of acute asthma, and suggest that their products may be used in monitoring asthma attack. Serum IL-5 and IFN-γ levels are not appropriate for use in the follow-up of asthmatic children.